Breaking new ground in protein detection: Self-supervised machine learning and iSCAT enable label-free detection of single proteins below 10 kDa - Dahmardeh, Mahyar; Dastjerdi, Houman Mirzaalian; Mazal, Hisham; Köstler, Harald; Sandoghdar, Vahid (Bio-Optics: Design and Application in Proceedings Biophotonics Congress: Optics in the Life Sciences 2023, OMA, NTM, BODA, OMP, BRAIN 2023, 2023)
Interferometric scattering (iSCAT) microscopy detects single nanoparticles in a label-free fashion. Utilizing self-supervised machine learning pushes the detection sensitivity of iSCAT to very small proteins and disease markers such as chemokines and cytokines.
CRIS-Team Scopus Importer:2024-12-16